Drying Of Empty Fruit Bunches (EFB) Using A Solar Drying System Of Double Pass Solar Collector With Porous Media - Aliasak, Zalila (2011)

(untitled)
In this thesis, the design of a solar drying system of a double-pass solar collector with porous media is presented. The system was constructed based on suggestions made by Ooi [1] and developed to dry empty fruit bunches (EFB) to moisture content of less than 10 mf wt%. Two sets of sample were prepared for this purpose, which is the treated sample and the untreated sample. From the results obtained, the temperature of the absorber plate of the solar collector of up to 100oC was recorded with solar radiation intensity of above 800Wm-2.